Les actes des évêques d’Avranches, ca. 990-1253 : esquisse d’un premier bilan - Richard Allen (Tabularia)
While the acta of other Norman dioceses, such as Bayeux, Évreux and Rouen, have been the subject of critical studies since the 1970s, those of the bishops of Avranches remain relatively unknown. Of course, the history of the diocese of Avranches, which was the smallest as well as the poorest of the ecclesiastical province of Rouen, is marked by some of the greatest misfortunes to befall the duchy’s patrimony (the collapse of the cathedral, the destruction of the archives of Saint-Lô), but enough material does survive to allow not only for an insight into one of the lesser-known episcopal chanceries of Normandy, but also for the opportunity to better understand numerous historical, diplomatic, archaeological, prosopographical and topographical facts.